Quantitative Recombination and Transport Properties in Silicon from Dynamic Luminescence - Giesecke, Johannes. (Springer Theses, Recognizing Outstanding Ph.D. Research, 2014)
Harmonically modulated luminescence combines the advantages of highly sensitive luminescence metrology with an immediate dynamic access to carrier lifetime in semiconductors at a minimum of required a priori information. The present work covers theoretical, conceptual, and experimental advances of the harmonically modulated luminescence technique. Theoretical constraints of dynamic carrier lifetime techniques are rigorously elaborated, including the proof of their differential nature and their characteristics at nonuniform spatial distributions of recombination rate. The pathway toward a unified, reliable, and versatile harmonically modulated carrier lifetime metrology is delineated - covering the entire solar cell production chain from bare ingots to finished solar cells. Accurate access to miscellaneous relevant recombination and transport properties via harmonically modulated luminescence is demonstrated and experimentally validated, embracing injection-dependent carrier lifetimes at extremely low injection conditions, a spatially resolved carrier lifetime calibration of luminescence images, and accurate approaches to both net dopant concentration and minority carrier mobility.